Windpipe Controls Drosophila Intestinal Homeostasis by Regulating JAK/STAT Pathway via Promoting Receptor Endocytosis and Lysosomal Degradation. - Ren, W.; Zhang, Y.; Li, M.; Wu, L.; Wang, G.; Baeg, G.H.; You, J.; Li, Z.; Lin, X. (PLoS Genetics, 2015)
The adult intestinal homeostasis is tightly controlled by proper proliferation and differentiation of intestinal stem cells. The JAK/STAT (Janus Kinase/Signal Transducer and Activator of Transcription) signaling pathway is essential for the regulation of adult stem cell activities and maintenance of intestinal homeostasis. Currently, it remains largely unknown how JAK/STAT signaling activities are regulated in these processes. Here we have identified windpipe (wdp) as a novel component of the JAK/STAT pathway. We demonstrate that Wdp is positively regulated by JAK/STAT signaling in Drosophila adult intestines. Loss of wdp activity results in the disruption of midgut homeostasis under normal and regenerative conditions. Conversely, ectopic expression of Wdp inhibits JAK/STAT signaling activity. Importantly, we show that Wdp interacts with the receptor Domeless (Dome), and promotes its internalization for subsequent lysosomal degradation. Together, these data led us to propose that Wdp acts as a novel negative feedback regulator of the JAK/STAT pathway in regulating intestinal homeostasis.